Boron Isotopes in the Mount Vulture Groundwaters (Southern Italy): Constraints for the Assessment of Natural and Anthropogenic Contaminant Sources. (2nd April 2019) - Paternoster, Michele
Abstract : The Mt. Vulture volcanic aquifer is an important reservoir of effervescent mineral water in southern Italy. This area is included in the Vulture Regional Park and is located on a popular tourist route for its high scenic and ecological value. Unfortunately, signs of anthropogenic impact have recently increased. Among minor elements, boron and its isotopes are considered useful environmental tracers since different anthropogenic and natural sources can be distinguished. In this study, B content and ( δ 11 B) isotope composition were determined in the Mt. Vulture groundwaters. The groundwater chemistry is strongly influenced by input of CO2 -rich volcanic gases, and two different hydrofacies are observed. The first water type (BAW) has bicarbonate alkaline and alkaline-earth composition and relatively low salinity, whereas the second one (HSW) has bicarbonate-sulphate alkaline composition and higher salinity. The HSW are enriched in boron and have low δ 11 B values (from –9.6‰ to –4.3‰) similar to those measured in the local magmas suggesting that B contents in these waters are influenced by prolonged interaction between local meteoric water and volcanic rocks. As to BAW, a wide variability in B concentrations (from 14 μ g/l to 769 μ g/l) and B isotope composition (from -16.1‰ to +23‰) has been observed. A possible anthropogenic input is thought to be responsible for such variability. The water samples with high B concentrations and negative δ 11 B values (−12.2‰ to −16.1‰) are probably influenced by agricultural activities; for water samples characterized by positive δ 11 B values (from +5.8‰ to +7.9‰) and low B contents, a slight contamination by sewage effluents cannot be excluded. These conclusions are also supported by B/Cl molar ratios (7.8 E − 3 to1.6 E − 2 ) different from those of the HSW group (1.1 E − 2 to7.0 E − 2 ). This study highlights that also in the Mt. Vulture volcanic area B isotopes coupled to the B/Cl ratio can be a useful tool for the assessment of natural and anthropogenic contaminant sources.